Otimização da remoção biológica de nitrogênio de efluente de abate e industrialização de aves usando reator em bateladas sequenciais - Mees, Juliana Bortoli Rodrigues (2010)
Agro-industries stand out as large polluters in Brazil, particularly because of the large amounts of waste rich in organic substances, nutrients (especially nitrogen and phosphorus), solids, oils and greases. In this category, slaughterhouses and bird cold storage processing plants are known for their high pollution potential. The removal of nitrogen from wastewater is usually accomplished using biological conventional processes, by nitrification plus denitrification, involving aerobic and anaerobic phases that are generally carried out in separate reactors or by different aeration intervals. The sequencing batch reactor (SBR) uses multiple steps in the same reactor, which include filling, reaction, settling, withdrawal and idling. This study aimed to investigate how carbon:nitrogen ratios (COD/NO2 --N+NO3 --N) 3, 6 and 9, adjusted by manipueira (wastewater from cassava industry) and cycle time (CT) of 8,12 and 16 hours affects the nitrogen and organic matter removal from poultry wastewater, operating a sequencing batch reactor containing suspended biomass, in two different conditions: condition I, with the reaction step consisted by aerobic/anoxic phases and condition II, anoxic I/aerobic/anoxic II phases. It was also intended to optimize and validate the process of nitrogen removal in this type of effluent, to evaluate the reactor stability using Shewhart control charts for individual measures, and to study the kinetics behavior of organic matter (COD) and nitrogen (NH4 +-N, NO2 --N and NO3 --N) degradation. The conditions I and II were evaluated through factorial planning (32) and, in order to optimize the conditions obtained with the initial factorial design, it was used a central composite rotational design (CCRD) with four assays in levels -1 and +1, four assays on the axial points levels (-1.414 and +1.414) and five replicates at the central point (0). The nitrification process performance was evaluated by the efficiency of ammonia nitrogen removal (%), the pre-denitrification and denitrification processes by the efficiencies of nitrite and nitrate removal (%) and the whole process by total inorganic nitrogen removal (%). During the nitrification and denitrification processes, parameters like temperature, pH, alkalinity, redox potential, salinity and conductivity were monitored. The highest removal percentages of total inorganic nitrogen were obtained, for conditions I and II, at the cycle time range between 12 and 16 hours and the C/N ratio of 3 to 6, which showed average efficiencies of 80.76 and 85.57% in condition I, and 90.99 and 91.09% in condition II, respectively. Although the condition II obtained a higher removal percentage of total inorganic nitrogen, only condition I presented a regression statistically significant and predictive, with Fcal/Ftab values higher than 4 for all steps involved in nitrogen removal. Optimizing the condition I, the highest percentages of nitrogen removal were achieved with the cycle time of 16 hours and C/N ratio of 6, validated experimentally, achieving an overall removal of inorganic nitrogen of 85.83±0.87 %. Evaluating the reactor stability, the results of the 20 trials carried out with optimum conditions showed a total inorganic nitrogen average removal of 84.32±1.59% (CV=1.89%) and organic matter removal of 53.65±8.48% (CV=15.81%), considering the complete process (nitrification plus denitrification), being the process under statistical control. The evaluation of the kinetic behavior of nitrogen conversion indicated a possible reduction in the cycle time of the anoxic phase, since percentages of NO2 --N and NO3 -N removal higher than 90% were obtained in just one hour of denitrification.